(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
There is a large number and variety of uncertainties that relate to almost all areas of life and the activity of people. Based on numerous literature sources, this article classifies various uncertainties into the following large groups: (1) stochastic uncertainties and (2) numerical uncertainties, including fuzzy and possibilistic ones. The article presents general approaches to assessing uncertainties in each of these groups. In addition, the article presents the main characteristics of general uncertainty estimates and provides an illustrative example.